2015
DOI: 10.4103/1793-5482.162709
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcomes in brainstem glioma: An institutional experience

Abstract: Aim of the Study:This study was to analyze the clinical outcomes of brain stem glioma treated with radiation therapy (RT) in our institution.Material and Methods:Records of 48 patients with brainstem glioma treated between January 2007 and January 2013 were reviewed. Demographic variables, clinical variables, radiological findings and treatment details with respect to age, sex, location of tumor ( pontine Vs non pontine ), signs and symptoms, RT dose, follow up period and outcomes were recorded. Patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…It has been found that patients who had short interval of symptoms (< 3 months) had poor outcomes [7]. In contrast, in our study there was no such association.…”
Section: Discussioncontrasting
confidence: 91%
“…It has been found that patients who had short interval of symptoms (< 3 months) had poor outcomes [7]. In contrast, in our study there was no such association.…”
Section: Discussioncontrasting
confidence: 91%
“…Yamasaki et.al reported that a patient age <20 years was one of the poor prognostic factors in a retrospective study of 23 patients with diffuse brainstem gliomas [ 31 ]. Lachi et.al reported a similar result that pediatric age group (<15 years) was associated with worse prognosis than in adults (>=15 years) in a series of 48 patients with brainstem gliomas treated by radiation therapy [ 32 ]. Consistent with these previous studies, we showed that the children/adolescent group (0-19 years) had a shorter median overall survival than adults (20+ years) (10.0 months vs. 19.9 months, p=0.026, Figure 3 ).…”
Section: Discussionmentioning
confidence: 94%
“…[44][45][46] Malignant glioma has a poor prognosis despite the continuous progress in therapeutic technologies, including surgery, radiotherapy, photodynamic therapy, and chemotherapy. [44][45][46] Malignant glioma has a poor prognosis despite the continuous progress in therapeutic technologies, including surgery, radiotherapy, photodynamic therapy, and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%